Sonogashira coupling reactions of bromomaleimides: route to alkyne/cis-Alkene/Alkyl maleimides: synthesis of luffarin X and cacospongionolide C - Deore, Prashant S.; N. P. Argade (Journal of Organic Chemistry, 2012)
Palladium-catalyzed Sonogashira coupling reaction of bromomaleimides with a diverse range of terminal alkynes has been demonstrated to furnish the corresponding alkynylmaleimides in very good yields. This coupling reaction followed by selective reduction of the triple bond to single bond have been utilized as the decisive steps to accomplish the first total synthesis of natural products (+/-)-luffarin X and (+/-)-cacospongionolide C.

Reactivity umpolung in intramolecular ring closure of 3,4-disubstituted butenolides: diastereoselective total synthesis of paeonilide - Deore, Prashant S.; N. P. Argade (Organic Letters, 2013)
Remarkable reactivity reversal stratagem in 3,4-disubstituted butenolides under acidic conditions is described. Design of a suitably substituted multifunctional butenolide followed by an acid-catalyzed chemo- and diastereoselective intramolecular ring closure via the reactivity umpolung has been demonstrated to accomplish a concise total synthesis of paeonilide. Overall, the present protocol involves one-pot reduction of an a,alpha,beta-unsaturated carbon carbon double bond and intramolecular nucleophilic insertion of oxygen function at the electron-rich gamma-position of butenolide. The involved mechanistic aspects have also been discussed.

Base-stimulated 1,2-, 1,4-, and 1,6-eliminations in suitably substituted alkylidenesuccinates leading to natural and unnatural conjugated alkenyl(methyl)maleic anhydrides - Deore, Prashant S.; N. P. Argade (Journal of Organic Chemistry, 2014)
With dimethyl maleate as the starting material, facile stereoselective syntheses of natural and unnatural conjugated alkenyl(methyl)maleic anhydrides have been described. The key reactions were base-endorsed novel 1,2-, 1,4-, and 1,6-eliminations in the corresponding alkylidenesuccinate derivatives. The 1,2-eliminations in cyclic carbonate and sulfite by regioselective abstraction of methine protons with the respective release of CO2 and SO2 provided a conjugated ketone product. The characteristic 1,4- and 1,6-elimination reactions with respective release of acetone and mesylate furnished the corresponding unsaturated alcohols. The obtained allylic alcohols were transformed into conjugated alkenyl(methyl)maleic anhydrides via oxidation followed by a Horner-Wadsworth-Emmons reaction pathway in very good yields. The mechanistic aspects involved in these significant elimination reactions have also been described in brief.

Concise account of the chemistry of valuable alkyl(methyl)maleic anhydrides - Deore, Prashant S.; Haval, Kishan P.; Gadre, Smita R.; N. P. Argade (Synthesis-Stuttgart, 2014)
A large number of significant bioactive natural and synthetic alkyl(methyl)maleic anhydrides are known in the contemporary literature. A broad range of suitably functionalized substrates have been tailored to accomplish concise and efficient syntheses of an array of alkyl(methyl)maleic anhydrides employing a variety of elegant synthetic strategies. This review presents a brief literature account of the isolation and activity of these important target compounds with a special emphasis on their synthesis.
Keywords: alkyl(methyl)maleic anhydrides; bioactivity; dimethylmaleic anhydride; isolation; nucleophilic reactions; Total synthesis

Metal-catalyzed cross-coupling reactions of halomaleic anhydrides and halomaleimides: synthesis of structurally interesting and biologically important natural and unnatural products - Deore, Prashant S.; N. P. Argade (Synthesis-Stuttgart, 2014)
This brief review presents a concise literature account of the metal-catalyzed cross-coupling reactions of halomaleic anhydrides and halomaleimides leading to significant synthetic and natural products. Metal-catalyzed Heck, Suzuki-Miyaura, Stille-Migita, Negishi, Hiyama, and Sonogashira cross-coupling reactions with palladium as the key element are discussed. The metal-catalyzed exchange of a vinylic leaving group by a carbon nucleophile, the SNV reaction, gives a diverse range of bioactive natural and unnatural products.
Keywords: bioactive natural and unnatural products; halomaleic anhydride; halomaleimide; metal-catalyzed cross-coupling; synthesis

Synthesis of chenopanone - Deore, Prashant S.; N. P. Argade (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2014)
Starting from glyoxalic acid, a facile three step approach to chenopanone has been described utilizing the Barbier reaction as a key step.
Keywords: acid hydrolysis; Barbier reaction; chenopanone; condensation; Glyoxalic acid; isovaleraldehyde; synthesis

Synthesis of yangjinhualine A - Deore, Prashant S.; Batwal, Ramesh U.; N. P. Argade (Synthesis-Stuttgart, 2015)
Selective reduction of 3-(4-hydroxyphenyl)-2-methylmaleic anhydride provides access the corresponding gamma-hydroxybutenolide natural product yangjinhualine A.
Keywords: anhydrides; lactones; Natural products; reduction; Regioselectivity